(3GdJPcQI HCMhGd GdehJi hGdCNQIs - (3eMeO Hf CMeO Hf CHj HcQ Hf aQM GdCfUGQj GdNRQLj GdCfOdSj, CHh YHO Gddg, GdbQWHj,J (B671 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYdj GdCYdi Gdhdj Gdehdi GdPj Ndb aCMjG hMce Ydi Ndbg HGdehJ s
(3BNQgG (B:s
(3MJi jCJjge CeQ Gddg Je HMeOGddg s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B239s
Keywords: (3GdJUha hGdBOGH GdTQYjIs